Features of compressed natural gas physical distribution: A Bulgarian case study - Miroslav Stefanov (Logistics, 2018)
Building a competitive and resource-efficient transportation system involves the achievement of a number of ambitious goals. Two of the main instruments in the European transportation policy in this field address the significant reduction of GHG emissions and oil dependency in transportation. Alternative fuels and compressed natural gas (CNG) in particular have huge potential for achieving these goals. The main problem that limits its wide utilization is related to the insufficient number of CNG refueling stations, especially along highways and routes from the core TEN-T network where no gas pipelines are available. Therefore, the aim of this research is to study a possible solution to building daughter CNG refueling stations which can be used as basis for formulating some recommendations for their accelerated construction along TEN-T core network as well as providing some initial knowledge to be used later for more comprehensive research. The research is based on the case-study method, which allows the presentation of the described best practice. The process of data collection is based on semi-structured interviews, study of normative documents, observation of daily sales and direct observations which were processed with the help of qualitative and quantitative methods for time series analysis-trend and seasonal component as well as descriptive statistics tools. Scientific literature and research as well as secondary data provided by international institutions are also used.
Keywords: 650; physical distribution; logistics activities; compressed natural gas (CNG); CNG refueling stations; daughter CNG refueling station; CNG refueling infrastructure